The Influence of Tourist Perceived Risk on Behavioral Intention : An Empirical Study on Palayangan Adventure River Rafting Pangalengan Tourists in the New Normal Era - Tazkiyyah, Maulida Kasyfiyatul (SABA: Journal of Tourism Research, 2023)
This research aims to investigate the influence of tourist perceived risk on behavioral intention by conducting a survey among tourists at Palayangan Adventure River Rafting in Pangalengan, Bandung Regency, during the New Normal era. The survey was conducted in 2021 (January - October) with the participation of 109 tourists. Convenience sampling was employed as the sampling technique, and multiple regression was used for data analysis. The research findings indicate that respondents provided positive and high assessments of perceived risk, consisting of dimensions such as functional risk, physical risk, psychological risk, social risk, and financial risk. Among these dimensions, physical risk received the highest rating, demonstrating that Palayangan Adventure River Rafting places a strong emphasis on the safety of tourists. However, the functional risk dimension received the lowest rating, indicating the need for improvements in promotional efforts. Furthermore, respondents' reactions regarding behavioral intention, such as positive word of mouth, recommendations to visit, and the intention to revisit, indicate that tourists tend to recommend Palayangan Adventure River Rafting due to the products and services offered meeting the tourists' needs.